2016
DOI: 10.2298/tsci140926146m
|View full text |Cite
|
Sign up to set email alerts
|

Effects of piston speed, compression ratio and cylinder geometry on system performance of a liquid piston

Abstract: Energy storage systems are being more important to compensate irregularities of renewable energy sources and yields more profitable to invest. Compressed air energy storage systems provide sufficient of system usability, and large scale plants are found around the world. The compression process is the most critical part of these systems and different designs must be developed to improve efficiency such as liquid piston. In this study, a liquid piston is analyzed with CFD tools to look into the effect of piston… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…Similar tendency was also reported by Coetzee et al [27] by applying the moving boundary of a solid piston in a 2D axisymmetric CFD model. Mutlu & Kiliç [28] showed that the compression efficiency decreased with the increasing piston speed, especially at high compression ratio (CR) and high L/D ratio of the LP column.…”
mentioning
confidence: 99%
“…Similar tendency was also reported by Coetzee et al [27] by applying the moving boundary of a solid piston in a 2D axisymmetric CFD model. Mutlu & Kiliç [28] showed that the compression efficiency decreased with the increasing piston speed, especially at high compression ratio (CR) and high L/D ratio of the LP column.…”
mentioning
confidence: 99%
“…Since a constant liquid volume flow rate is often assumed by the liquid pump, the liquid velocity as well as the Re L are considered thereby as constant during the compression process. On the contrary, the gas flow is much more complex than a simple pipe flow because the gas does not have the same velocity as water all over the piston column, as reported by Mutlu & Kiliç [52] and Schober et al [45]. It has been observed by Neu et al [53,27] that during compression many re-circulation zones could appear next to the walls (upper, bottom and lateral) of the piston column.…”
Section: Flow Patterns During Air Compressionmentioning
confidence: 97%
“…Mutlu & Kiliç [52] have numerically examined the effect of piston speed, the CR and the cylinder geometry on η c and required power of a LP. It was found that the η c decreased from 87.93% to 68.89% when CR increased from 5 to 80.…”
Section: Thermodynamic Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional Liquid Piston Compressor can be parametrised in the context of geometry and operations. Effect of the compression speeds and compression ratios was the topic of the study performed by Motlu et.al [5]. It was also found out that efficiency of such device rise when length to bore diameter ratio is increased [6].…”
Section: Introductionmentioning
confidence: 98%